The Wanderer - Creech, Sharon; Diaz, David (New York : Scholastic, 2001)
Thirteen-year-old Sophie and her cousin Cody record their transatlantic crossing aboard the Wanderer, a forty-five foot sailboat, which, along with uncles and another cousin, is en route to visit their grandfather in England.
Newbery Honor book for 2001.
Keywords: Sailboats -- Juvenile fiction; Sailing -- Juvenile fiction; Ocean travel -- Juvenile fiction; Families -- Juvenile fiction; Grandfathers -- Juvenile fiction; Sea stories -- Juvenile fiction